Learning in the ED: chaos, partners and paradoxes. Issue 6 (12th August 2019) - Hussain, Aman; Rossi, Tony; Rynne, Steven
Abstract : Purpose: Most contemporary research in medical education focuses on the undergraduate component conducted within medical schools. The purpose of this paper, however, is to better understand how medical residents and practicing attending physicians learned to practice within the context of the emergency medicine department (ED) workplace. Design/methodology/approach: In all, 18 residents and 15 attending physicians were interviewed about their learning in the ED. Interviews were digitally recorded and transcribed verbatim then analysed using an iterative approach. Emergent themes were shared with the participants to ensure they were an accurate representation of their lived experiences. Findings: The first of the three main findings was that the ED learning environment was characterised as "messy" because of the inherently chaotic nature of the workplace. The second finding was that patients and nurses were informal partners in learning. The third main finding was that learning and working in the ED can be difficult, isolating and often lacks continuity. Research limitations/implications: The main limitation associated with this research relates to the highly situated and contextually bound nature of this study. Nevertheless, the findings should be generative for others interested in supporting the work and learning of health professionals. Originality/value: This study shifts the focus in medical education research from formal undergraduate education to learning in high stress and chaotic workplaces. Accordingly, this work provides valuable insights for others interested in the messy realities of learning in professional practice.